MAKNA MITSAQAN GHALIZA DALAM AL-QUR'AN (STUDI TAFSIR TEMATIK) - Diah Ramadhani; Nurfadhilah Syam; Muhammad Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research examines the meaning of the word "mitsāqan ghalīẓā" in the Qur'an by placing it within the entire context of its usage, namely in the covenant of Allah with the prophets, the covenant of Allah with the Children of Israel, and the marriage contract. This emphasis on the scope is intended to demonstrate that the meaning of "mitsāqan ghalīẓā" represents a universal covenant in the Qur'an that reflects the highest divine commitment, rather than being limited solely to the institution of marriage. This study is a library research utilizing a thematic interpretation approach (maudhu‘ī). Data is obtained through the exploration of Qur'anic verses that contain the meaning of "mitsāqan ghalīẓā" and is analyzed based on classical and contemporary interpretations, including Tafsir al-Qur’an al-‘Aẓīm by Ibn Kathir, Tafsir an-Nūr by Tengku Muhammad Hasbi Ash-Shiddiqie, and Tafsir al-Mishbah by M. Quraish Shihab. The results of the study indicate that "mitsāqan ghalīẓā" means a very strong, sacred, and binding covenant that carries significant responsibility before Allah. In the context of marriage, "mitsāqan ghalīẓā" reflects the sanctity of the marriage contract as a divine trust that demands responsibility, justice, and fidelity. Thus, the meaning of the word "mitsāqan ghalīẓā" has strong relevance in the lives of Muslims.